2023
DOI: 10.1117/1.jmi.10.2.023502
|View full text |Cite
|
Sign up to set email alerts
|

Timing resolution in double-sided silicon photon-counting computed tomography detectors

Abstract: Purpose: Our purpose is to investigate the timing resolution in edge-on silicon strip detectors for photon-counting spectral computed tomography. Today, the timing for detection of individual x-rays is not measured, but in the future, timing information can be valuable to accurately reconstruct the interactions caused by each primary photon.Approach: We assume a pixel size of 12 × 500 μm 2 and a detector with double-sided readout with low-noise CMOS electronics for pulse processing for every pixel on each side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Current semiconductor detectors used for photon counting imaging can only reach 1 ns resolution for TOF x-ray measurements (Sundberg et al 2023), making scintillators the only option. Counting individual photons using scintillators is a challenge because the large decay time of common materials makes separating events difficult, but it was recently shown that sufficient count rate was achievable using LuAP: Ce and LaBr 3 (van der Sar et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Current semiconductor detectors used for photon counting imaging can only reach 1 ns resolution for TOF x-ray measurements (Sundberg et al 2023), making scintillators the only option. Counting individual photons using scintillators is a challenge because the large decay time of common materials makes separating events difficult, but it was recently shown that sufficient count rate was achievable using LuAP: Ce and LaBr 3 (van der Sar et al 2021).…”
Section: Discussionmentioning
confidence: 99%